The Effect of of Long-Term Headset Use on Changes in Human Head Structure - Chandra, Alfateh Farhanz; Halim, Anna Gracia; Louis, Robbin Stephen; Rahardjo, Benedictus (Universitas Muhammadiyah Tangerang, 2025)
Headsets are essential for daily activities such as gaming, working, and online learning. However, uneven mechanical pressure generated by excessive use of headsets can affect the skull structure. This innovative headset features a Dual-Support System that distributes pressure evenly, lightweight ergonomic pads, and an adjustable design to fit the user's head and ear size. In this study, design elements, ergonomics, and health risks associated with long-term headset use were evaluated through observation, ergonomic studies, and anthropometric measurement methods. The results showed that this design is effective in reducing the risk of skull deformation and making the headset more comfortable to use. In addition, the research also supports the achievement of Sustainable Development Goals (SDGs) 3 and 8 as it promotes health well-being and improve working conditions for individuals in digital and creative fields, who rely on headset for prolonged periods. Through an intensive study of ergonomic methods and the integration of SDG principles, this research not only addresses physical health concerns but also contributes to creating a more sustainable, productive, and comfortable environment